2021
DOI: 10.1016/j.cgh.2020.09.035
|View full text |Cite
|
Sign up to set email alerts
|

Potential Benefit With Complementary and Alternative Medicine in Irritable Bowel Syndrome: A Systematic Review and Meta-analysis

Abstract: Background and Aims: Patients with irritable bowel syndrome (IBS) may pursue complementary and alternative medicine (CAM). We conducted a comprehensive systematic review and meta-analysis examining efficacy of CAM vs. placebo or sham in adults with IBS. Methods: Publication databases were searched for randomized controlled trials of CAM therapies (herbal therapy, dietary supplements, mind-body based, body-based, and energyhealing) in adults with IBS. Data were extracted to obtain pooled estimates of mean impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 87 publications
0
18
0
Order By: Relevance
“…More and more patients are forced to seek complementary and alternative therapies because of the adverse effects and side effects of drugs [12][13][14]. Acupuncture and moxibustion are the effective treatment for IBS [12,14], and there are several meta-analyses suggested bene ts of acupuncture and moxibustion in terms of symptom control and quality of life improvements in patients with IBS [13,15].…”
Section: Introductionmentioning
confidence: 99%
“…More and more patients are forced to seek complementary and alternative therapies because of the adverse effects and side effects of drugs [12][13][14]. Acupuncture and moxibustion are the effective treatment for IBS [12,14], and there are several meta-analyses suggested bene ts of acupuncture and moxibustion in terms of symptom control and quality of life improvements in patients with IBS [13,15].…”
Section: Introductionmentioning
confidence: 99%
“…is observation is consistent with a recent systematic review that recommended using an optimal placebo as a control, defined as an experience comparable to the intervention. In the case of an inadequate placebo, the response would be more favorable to the intervention [35]. However, choosing the adequate sham therapy, especially in the field of body-directed therapies, is a difficult task.…”
Section: Discussionmentioning
confidence: 99%
“…Hypnotherapy became popular in the 1980s, when an RCT demonstrated some therapeutic effectiveness [21]. In recent years, hypnotherapy has shown a beneficial impact on IBS symptoms [22][23][24][25][26][27][28][29][30][31][32][33][34] and according to Billings et al [35], mind-body therapies, dietary supplements, and herbal medicine have been shown to be beneficial for abdominal pain and overall IBS symptoms in a setting where evidence of effectiveness is weak.…”
Section: Introductionmentioning
confidence: 99%
“…There was no benefit over placebo for abdominal pain, however, for body-based and energy healing therapies. 89 Currently the evidence would not support use of complementary or alternative medicine approaches for IBS pain.…”
Section: Several Complementary and Alternative Medicine Approachesmentioning
confidence: 99%